Engaging in digital technology: one size fits all?. Issue 7 (8th July 2014) - Lichy, Jessica; Khvatova, Tatiana; Pon, Kevin
Abstract : Purpose: – The purpose of this paper is to provide an insight into the extent to which faculty have adopted technology-enhanced learning in the delivery of undergraduate programmes to a largely international cohort, and indirectly the barriers that may be preventing a more widespread use of technology. Design/methodology/approach: – The enquiry takes a cross-disciplinary approach to explore how technology is used in the delivery of international programmes in France and Russia; the focus lies at the intersection of technology-led learning and managing cultural diversity. A face-to-face survey is used to gather the more specific information about teaching practices at each institution. Findings: – The findings of the survey strongly suggest that technology acceptance and technology awareness are influenced by a number of complex factors in this particular cultural context. The study concludes by discussing various recommendations for integrating technology into courses delivered across the partner institutions. Research limitations/implications: – The two institutions are based in "second cities" but they do not reflect a nation-wide attitude to using technology for teaching purposes. The findings cannot be extrapolated beyond this relatively restricted geographic sample. Originality/value: – Existing studies often discuss and compare student reactions to technology-enhanced learning but there is a gap in the understanding of the broader factors that can influence the delivery of course materials using technology. The perception and usage of internet technology can vary considerably across different cultures and linguistic communities, and this factor can have an impact on the way a course is delivered.